Musyawarah dan Saling Menghormati Antara Suami Istri: Kajian Tafsir Tematik Atas Prinsip Keharmonisan Keluarga (Menjelaskan Nilai Syura dalam Relasi Rumah Tangga dan Pengasuhan Anak) - Siti Masitoh; Ali Khosim; Athoillah Athoillah (JURNAL ILMIAH NUSANTARA, 2026)
Human well-being, peace, and tranquility can be achieved and begin with a harmonious household. A safe home, characterized by mutual love and respect, will produce good individuals who will not disturb the atmosphere or pose a danger to society. Implementing the concept of a harmonious family requires a strong commitment from each family member. This involves a willingness to support, respect, and understand one another. This paper uses qualitative research, which examines social phenomena from the perspective of participants. In traditional husband-wife relationships, there is a division of duties and roles between husband and wife. The husband is responsible for earning a living, while the wife is responsible for managing the household and raising children. Male leadership over women is not a form of discrimination against women, but rather a form of Islamic respect for women's status as wives who must be protected.